The Role and Importance of the Treaty of Medina in Establishing a Peaceful State of Medina: پر امن ریاست مدینہ کے قیام میں میثاقِ مدینہ کا کردار اور اہمیت - Ali, Ajmal; Al-Azhari, Dr. Ali Akbar (Al-Irfan, 2021)
The Holy Prophet Muhammad (PBUH) established several treaties to promote peace and good relations with neighboring tribes and countries of the Islamic State of Medina, notably the Treaty of Medina. This landmark agreement integrated Jews and Muslims into a unified community, recognizing the Prophet (PBUH) as their leader and committing to his decisions in disputes. It included a mutual defense pact and was founded on progressive principles of citizenship and the rule of law, ensuring individual rights and equality before the law. The Treaty of Medina marked the first comprehensive legal framework in history, fostering a multicultural society characterized by moderation, tolerance, and respect for human dignity. This document is essential for understanding the humanitarian dimensions of the Prophet’s treaties, promoting human values and coexistence, and advocating for harmony among diverse nations, countering the idea of a "clash of civilizations.".